United States : 2017 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that the United States is in the longest expansion since 1850. The unemployment rate has fallen to 4.4 percent and job growth continues to be strong. The economy has gone through a temporary growth dip in the early part of 2017, but momentum has picked up. The economy is expected to grow at 2.1 percent in 2017 and 2018, supported by solid consumption growth and a rebound in investment. Over the next 12-18 months, personal consumer expenditure inflation is expected to slowly rise above 2 percent, before returning to the Federal Reserve's medium-term target of 2 percent.